Corporate Social Responsibility (CSR) Disclosure on the Application of Conservatism: The Role of Foreign Ownership as a Moderating Variable - Sari, Maria Puspita Nugrahaning; Setiawan, Doddy (Jurnal Keuangan dan Perbankan, 2023)
This research aimed to determine what factors affect manufacturing companies' application of accounting conservatism. In addition, this study examines two factors: (1) the effect of CSR disclosure on the application of conservatism in manufacturing firms; and (2) the effect of foreign ownership on the relationship between CSR disclosure and the application of conservatism in manufacturing firms. This study was quantitative. This study utilised annual and sustainability reports from 2018 to 2022 from manufacturing companies listed on the Indonesia Stock Exchange. The study examined 590 data using the Fixed Effect Model as a regression model to estimate panel data. The findings revealed two conclusions: a significant relationship between CSR disclosure and accounting conservatism, and foreign ownership weakened the correlation between CSR disclosure and accounting conservatism. This study employed firm size, profitability, leverage, and audit quality as control variables.